Challenges for Women in Political Spaces: Experiences of Former Woman Representatives of Local Government (Rigvedic Himalaya, 2025)
In Nepal, the provision of inclusiveness in laws play a significant role to increase the women’s participation in local government. In this context, this study explores the challenges to women’s engagement in public space, in particular at local government in Nepal. This study is primarily based on indepth interview with 10 Former Women Local Government Representatives (FWLGRs). Findings reveal that women’s experiences in local politics in Bagmati Province reflect broader global debates on gender participation in political and public spaces. Unlike to men, women in local politics face numerous challenges, including patriarchal attitudes, family obligations, economic barriers, gender-based violence, and caste-based discrimination, which appear as breakers to them to participate in public space. These obstacles often limit their ability to secure significant roles in public space. Legal reforms have created unprecedented opportunities, but without addressing structural inequalities—patriarchy, caste discrimination, economic exclusion, and political violence—the meaningful participation and representation of women in political and public spaces remains general, thin and weak that need to be addressed.